A novel de novo truncating variant in a Hungarian patient with CTNNB1 neurodevelopmental disorder - Nikoletta Nagy; Margit Pál; Dóra Nagy; Barbara Anna Bokor; Aliz Zimmermann; Balázs Gellén; András Salamon; László Sztriha; Péter Klivényi; Márta Széll (BMC, 2024)
Abstract Purpose We aimed to elucidate the underlying disease in a Hungarian family, with only one affected family member, a 16-year-old male Hungarian patient, who developed global developmental delay, cognitive impairment, behavioral problems, short stature, intermittent headaches, recurrent dizziness, strabismus, hypermetropia, complex movement disorder and partial pituitary dysfunction. After years of detailed clinical investigations and careful pediatric care, the exact diagnosis of the patient and the cause of the disease was still unknown. Methods We aimed to perform whole exome sequencing (WES) in order to investigate whether the affected patient is suffering from a rare monogenic disease. Results Using WES, we identified a novel, de novo frameshift variant (c.1902dupG, p.Ala636SerfsTer12) of the catenin beta-1 (CTNNB1) gene. Assessment of the novel CTNNB1 variant suggested that it is a likely pathogenic one and raised the diagnosis of CTNNB1 neurodevelopmental disorder (OMIM 615,075). Conclusions Our manuscript may contribute to the better understanding of the genetic background of the recently discovered CTNNB1 neurodevelopmental disorder and raise awareness among clinicians and geneticists. The affected Hungarian family demonstrates that based on the results of the clinical workup is difficult to establish the diagnosis and high-throughput genetic screening may help to solve these complex cases.